Pengaruh Job Insecurity Terhadap Motivasi Kerja Pada Guru Tidak Tetap Di Sma N.1 Uluidano Tae Nias Selatan - Suardin Halawa; Yamolala Zega; Eliagus Telaumbanua; Syah abadi mendrofa (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to determine job insecurity on work motivation of non permanent teachers at SMA negeri 1 uluidano tae south nias. Job insecurity is a condition where workers feel that their jobs are threatened and there is a powerlessness to do anything about the situation. Based on the phenomenon that occurred Guru Tidak Teltap at SMA N. 1 Ululidano Tae Nias Selatan which has a high level of job insecurity, this occurs because Guru Tidak Tetap often feels like he has lost his enthusiasm for teaching, because many students do not respect honorary teachers. This study aims to determine the Influence of Job Insecurity on Work Motivation in Non-Permanent Teachers at SMA N. 1 Ululidano Tael Nias Selatan. This study uses a qualitative research method, research that uses a qualitative method focuses its analysis, the respondents are Non-Permanent Teachers at SMA N. 1 Uluidano Tae Nias Selatan totaling 34 people. The results of the study were taken by distributing questionnaires that were tested based on the Classical Assumption Test, Simple Linear Regression and T Test. The results of the study showed that there was an influence between Job insecurity on work motivation with a sign value of 0.001 <0.05.